Procedural Control Versus Resources as Potential Origins of Human Hyper Selectivity - Ansorge, Ulrich; Büsel, Christian; Forstinger, Marlene; Gugerell, Daniel; Grüner, Markus; Pomper, Ulrich; Stolte, Moritz; Schmid, Rebecca Rosa; Valuch, Christian (Frontiers in Psychology, 2021)
In the current review, we argue that experimental results usually interpreted as evidence for cognitive resource limitations could also reflect functional necessities of human information processing. First, we point out that selective processing of only specific features, objects, or locations at each moment in time allows humans to monitor the success and failure of their own overt actions and covert cognitive procedures. We then proceed to show how certain instances of selectivity are at odds with commonly assumed resource limitations. Next, we discuss examples of seemingly automatic, resource-free processing that challenge the resource view but can be easily understood from the functional perspective of monitoring cognitive procedures. Finally, we suggest that neurophysiological data supporting resource limitations might actually reflect mechanisms of how procedural control is implemented in the brain.